2008
DOI: 10.1519/jsc.0b013e31818219cb
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Caffeine and Aspirin on Light Resistance Training Performance, Perceived Exertion, and Pain Perception

Abstract: This study compared independent effects of caffeine and aspirin on muscular endurance (repetitions), heart rate (HR), perceived exertion (RPE), and perceived pain index (PPI) during light resistance training bouts performed to volitional failure. It was hypothesized that the hypoalgesic properties of these ergogenic aids would decrease pain perception and potentially result in enhanced performance. College-aged men (n = 15) participated in a within-subjects, double-blind study with three independent, counterba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 26 publications
9
49
2
4
Order By: Relevance
“…However, as reported in a study involving analgesic medication and strength training 9 , the results of the present study suggest that the pain reduction promoted by the ibuprofen seems not to promote increase in performance in the exercise under study.…”
Section: Placebo or Ibuprofen Administrationsupporting
confidence: 58%
See 1 more Smart Citation
“…However, as reported in a study involving analgesic medication and strength training 9 , the results of the present study suggest that the pain reduction promoted by the ibuprofen seems not to promote increase in performance in the exercise under study.…”
Section: Placebo or Ibuprofen Administrationsupporting
confidence: 58%
“…However, this kind of issue is still limited in the literature áand, despite the belief from the part of athletes and coaches that some medication has ergogenic action; the scientific evidence so far reported is contradictory. While clinical assays have already demonstrated that the analgesic drug known as aspirin does not alter performance in incremental exercises 7 , exercises with predominately aerobic characteristic (ultra-marathon) 8 or anaerobic (strength training) 9 , evidence suggests that the analgesic paracetamol is able to reduce the time of cyclists in ten-mile events 10 . Concerning the NSAI, a limited number of evidence in humans suggests absence of benefits related to the pharmacological therapy in endurance exercises 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, em concordância com os resultados encontrados no presente estudo, outros autores têm demonstrado melhoras na performance de força muscular a 100% de 1RM no supino reto (Goldstein et al, 2010), a 80% de 1RM no supino reto (Beck et al, 2006) e cadeira extensora (Duncan, Lyons, & Hankey, 2009), e na carga de 12RM na cadeira extensora e bíceps apoiado na máquina (Hudson, Green, Bishop, & Richardson, 2008).…”
Section: Discussionunclassified
“…Em relação à dosagem administrada de cafeína (3-6 mg · kg -1 ) é independente do resultado apresentado na performance na força muscular máxima (Goldstein et al, 2010) ou submáxima (Beck et al, 2006;Duncan et al, 2009;Hudson et al, 2008) (Bell & Mclellan, 2002), baseando-se nas divergências apresentadas acima, pode-se prever que variações na intensidade e/ou duração dos testes de exercício, bem como a dosagem cafeína administrada, ou mesmo o intervalo de tempo entre a administração e o início dos testes e a frequência no consumo da cafeína são fatores que interferem efetivamente nos resultados. De facto, no presente estudo, nenhuma medida de sangue foi feita, assim só é possível a preocupação com os efeitos de desempenho na força submáxima, mas não sobre os efeitos nos intermediários plasmáticos.…”
Section: Discussionunclassified
“…Concordando com o estudo acima mencionado, Hudson et al (2008) avaliaram os efeitos da mesma dosagem aguda de cafeína (6 mg/kg) sobre o número de repetições executadas até a exaustão durante 4 séries nos exercícios leg press e flexão de cotovelo mediante uma carga de 12-RM. Foi verificado que a cafeína foi eficaz em aumentar o número de repetições até a exaustão na primeira série do exercício de membro inferior (16,0 ± 1,9 vs. 13,5 ± 2,5) em comparação à condição placebo.…”
Section: Efeitos Sobre O Desempenho De Forçaunclassified